An investigation of using moringa oleifera seeds oil as lubricant - Mohd Mizuan, Omar (2013)
Many liquids, including water have been used as lubricants since the Roman era to minimize the friction, heat, and wear between mechanical parts in contact with each other. Today, lubricating oil, or lube oil, is the most commonly used lubricant because of its wide range of possible applications. Recently, pollution and environmental health aspects have become increasingly important as public issues. The increased environmental awareness is a primary driving force for the new technological developments. Nowadays, the increasing application of biobased lubricants could significantly reduce environmental pollution and contribute to the replacement of petroleum base oils. Vegetable oils are recognized as rapidly biodegradable and are thus promising candidates for use as base fluids in formulation of environment friendly lubricants. Future lubricants also have to be more environmentally adapted, have a higher level of performance, and lower total life cycle cost (LCC) than presently used lubricants. Thus, this research aims to produce a standard lubricant from Moringa oleifera seeds oil which is more environmentally friendly and has higher level of performance based on ASTM standard. All the Moringa oleifera seeds have been dried at 70°C before the samples were grinded and sieved for 250μm in size by using grinder and sieve shaker. The Moringa oleifera seeds oil then was extracted by using 200mL n- hexane in soxhlet extractor with 10g of Moringa oleifera seeds. The sample was put into the rotary evaporator to remove the n-hexane and get the pure Moringa oleifera oil. The basic filtration was done to remove all the small particles in the oil. Then, some tests were conducted to measure the parameters and the correlation of the properties to the ASTM standards as light machine lubricant. From the experiments, the Moringa oleifera oil kinematic viscosity was 43.813 mm2/s at 40°C and 8.974 mm2/s at 100°C, density was 0.915 g/cm3, cloud point was 12°C, pour point was 8°C, and has viscosity index of 192. Therefore, it should be considered as lubricant for gear according to ASTM Standard